FAO/IBPGR technical guidelines for the safe movement of sweet potato germplasm - Moyer, J.W.; Jackson, G.V.H.; Frison, Emile A.; Food and Agriculture Organization of the United Nations (1989)
These guidelines are divided into 2 parts. The first makes general recommendations on how best to move Ipomoea germplasm and mentions available intermediate quarantine facilities. The second part covers the important insect pests and viral, mycoplasmal, bacterial and fungal diseases of quarantine concern. The information given on any particular pest or pathogen concentrates on those aspects most relevant to quarantine. (Abstract © CAB ABSTRACTS, CAB International)